Targeted analysis of dyslexia-associated regions on chromosomes 6, 12 and 15 in large multigenerational cohorts - Nicola H. Chapman; Patrick A. Navas; Michael O. Dorschner; Michele Mehaffey; Karen G. Wigg; Kaitlyn M. Price; Oxana Y. Naumova; Elizabeth N. Kerr; Sharon L. Guger; Maureen W. Lovett; Elena L. Grigorenko; Virginia Berninger; et al. (PLoS ONE, 2025)
Dyslexia is a common learning impairment with a genetic basis that affects word reading and spelling. An increasing list of loci and genes have been implicated, but analyses to-date have investigated only limited genomic variation within each locus with no confirmed pathogenic variants identified. Our study is the first to comprehensively sequence both coding and cis-acting regulatory regions of such genes in a large study sample. In a collection of >2000 participants in families from three independent sites, we performed targeted capture and comprehensive sequencing of all exons and some regulatory elements of five candidate risk genes ( DNAAF4 , CYP19A1 , DCDC2 , KIAA0319 and GRIN2B ) for which prior evidence for a role in dyslexia exists from more than one sample. We evaluated evidence for association in each of six dyslexia-related quantitative phenotypes (traits) using both individual common single nucleotide polymorphisms and aggregated rare variants. We detected no promoter alterations and few deleterious variants in the coding exons, none of which showed evidence of association with any trait. Single variant and aggregate testing of DNAAF4 failed to detect significant evidence of association with any of the traits. The other four genes provided evidence of association with one or more traits. A common variant downstream of CYP19A1 showed significant evidence of association with multiple traits with or without verbal IQ (VIQ) adjustment. A haplotype that stretches from the downstream region of KIAA0319 to the second intron of DCDC2 was associated with reduced performance on timed real word reading. Finally, rare exonic variants in GRIN2B were associated with performance on spelling, with or without adjustment for VIQ. Our findings from this large-scale sequencing study complement those from genome-wide association studies, argue against the causative involvement of large-effect coding variants in these five candidate genes, support a multigenic etiology, and suggest a role of transcriptional regulation.